Investment Restrictions and Contagion in Emerging Markets - Ilyina, Anna (IMF Working Papers; Working Paper, 2005)
The objectives of this paper are: (1) to analyze an optimal portfolio rebalancing by a fund manager in response to a "volatility shock" in one of the asset markets, under sufficiently realistic assumptions about the fund manager's performance criteria and investment restrictions; and (2) to analyze the sensitivity of the equilibrium price of an asset to shocks originating in other fundamentally unrelated asset markets for a given mix of common investors. The analysis confirms that certain combinations of investment restrictions (notably short-sale constraints and benchmark-based performance criteria) can create additional transmission mechanisms for propagating shocks across fundamentally unrelated asset markets. The paper also discusses potential implications of recent and on-going changes in the investor base for emerging market securities for the asset price volatility.